Relationship between Preparation and Attitude in 3-4 Year Old Children regarding Newborn Sibling - Andika Sari, Diah; Nuryuliani, Eneng; Prapti, Ndaru; Pasco Bayan, Rocelia (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2022)
Purpose – The aim of this study was to determine the relationship between the preparation for a newborn sibling and the attitude of children aged 3 to 4 years. This study was carried out in Kemayoran District, Central Jakarta.Design/methods/approach – The method used was a correlational quantitative research method. The sampling method was carried out using the one stage cluster sampling method from 8 sub-districts in Kemayoran District, Central Jakarta, Indonesia. A total of 240 mothers who have children aged 3-4 years with younger siblings were taken as samples. Data collection technique used was a questionnaire.Findings – While the results of the study obtained a Pearson correlation coefficient of 0.589, the results of the t test showed that tcount was 11.235> ttable namely, 1.651. It means there was a significant positive relationship between the preparation for a newborn sibling and the attitude of children aged 3-4 years. The coefficient of determination test results calcuated by SPSS v.22 program obtained R2 of 0.347 or KD of 34.7%. This means that the preparation for a newborn sibling was able to explain 34.7% of the attitude of children aged 3-4 years. Meanwhile, the remaining 65.3% was influenced by other variables which were not included in this study.Research implications/limitations – This study was limited to simple correlational research with one independent variable and one dependent variable. Future studies can explore greater with other related variables. Practical implications – From this study, it can be concluded that there was a significant and positive relationship between the preparation for a newborn sibling with the attitude of early childhood children aged 3-4 years.Originality/value – With careful preparation, parents who prepare for the arrival of a new sibling can form a positive attitude response in children aged 3-4 years. Paper type Research paper